Pengaruh Media Adobe Flash terhadap Minat Belajar Siswa Kelas VI SDN Kepatihan 1 pada Materi IPS - Asnah, Nurul; Wachidah, Kemil (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The purpose of this study was to determine the effect of using AdobeFlash media on the interest in social studies learning for grade VI students at SDNKepatihan 1. This study used a quantitative research method of Pre ExperimentalDesign with the form of design used was One Group Pretest-Posttest. Thepopulation in this study were all students of class VI SDN Kepatihan 1 totaling 29.The sample was taken using saturated sampling with a sample of 29 students. Thedata collection technique used is a test, namely the Likert psychological testinstrument. The results of the hypothesis test using the test Paired Sample T-Test.In the one-tailed hypothesis test to the right of interest in learning, the value is0.000 <0.05, then H0 is rejected, H1 is accepted, so it can be concluded that there isa positive and significant influence in the use of Adobe Flash media on the interestin learning social studies for grade VI students of SDN Kepatihan 1. LearningMedia; Interest in Learning; Social Studies